Fluorescence quenching and bonding properties of some hydroxamic acid derivatives by iron(III) and manganese(II) - Senthilnithy, R.; Costa, M.D.P. De; Gunawardhana, H.D. (My University, 2008)
Spectrophotometric investigations of highly fluorescent metal chelating molecules are of relevance due to their potential application in novel, selective fluorescence-based sensors. Benzene and naphthalene chromophores are highly fluorescent while hydroxamic acids are widely used as ligands for complexation of transition metals. In order to develop fluorescence probes, several phenyl derivatives of N-phenylbenzohydroxamic acid and an aminodihydroxamic acid linked with a naphthalene chromophore were synthesized and their selective ionophoric properties towards iron(III) and manganese(II) ions were investigated using fluorescence and absorption spectroscopy. Both methods confirm the formation of 1:1 and 1:2 complexes for iron(III) and a 1:1 complex for manganese(II). The complex that is formed depends on the concentration of the ligand and pH of the medium. The amino dihydroxamic acid exhibits a prominent selectivity towards iron(III) with a two-step 1:1 and 1:2 quenching mechanism at pH 3 and towards manganese(II) with a 1:1 quenching mechanism at a probe concentration of 1 × 10-5 mol dm-3 at pH 9.5 The logarithm of overall formation constants of 1:1 and 1:2 complexes of iron(III) were estimated as 3.30 and 9.05, respectively.
Keywords: hydroxamic acid; fluorescence quenching; Stern–Volmer equation; fluorophore; isobestic point